Genetic Counseling Dilemmas for a Patient with Sporadic Amyotrophic Lateral Sclerosis, Frontotemporal Degeneration & Parkinson's Disease. Issue 3 (1st March 2017) - Mantero, Vittorio; Tarlarini, Claudia; Aliprandi, Angelo; Lauria, Giuseppe; Rigamonti, Andrea; Abate, Lucia; Origone, Paola; Mandich, Paola; Penco, Silvana; Salmaggi, Andrea
Abstract: Amyotrophic lateral sclerosis (ALS), frontotemporal degeneration and Parkinson's disease may be different expressions of the same neurodegenerative disease. However, association between ALS and parkinsonism‐dementia complex (ALS‐PDC) has only rarely been reported apart from the cluster detected in Guam. We report a patient presenting with ALS‐PDC in whom pathological mutations/expansions were investigated. No other family members were reported to have any symptoms of a neurological condition. Our case demonstrates that ALS‐PDC can occur as a sporadic disorder, even though the coexistence of the three clinical features in one patient suggests a single underlying genetic cause. It is known that genetic testing should be preferentially offered to patients with ALS who have affected first or second‐degree relatives. However, this case illustrates the importance of genetic counseling for family members of patients with sporadic ALC‐PDC in order to provide education on the low recurrence risk. Here, we dicuss the ethical, psychological and practical consequences for patients and their relatives.